STUDENTS’ PERCEPTION ON THE EFFECTIVENESS OF TEACHING ESP FOR SOCIAL AND POLITICAL SCIENCE PROGRAM - Nensy Triristina; Samsul Khabib (Universitas PGRI Madiun, 2021)
This study investigates ESP students' perception of ESP teaching effectiveness for Social and Political Science from the non-English Department. Data were collected from forty-six participants from three Social and Political Science Program Departments, Darul 'Ulum University. To obtain the data, questionnaires and interviews were employed as the instruments. Furthermore, the data were analyzed using descriptive analysis into four categories; material, teaching method, learning motivation, and classroom management. The findings showed that some students were dissatisfied with the ESP materials given. However, the students perceived that they need to take the ESP materials to have professional communication skills for future careers. Additionally, it was also found that the roles of lectures' guidance in learning ESP were important. Finally, the interview results reveal the difficulties the students face in learning ESP, including vocabulary, pronunciation, reading comprehension, and grammatical structure.